Religion as deliverance „policy” during exile. The case of the Romanian writer Vintila Horia - Orian, Georgeta (Balcanica Posnaniensia. Acta et studia, 2010)
This study explores the function of religion as a true „policy” of salvation during exile, through the example of the Romanian writer Vintilă Horia (1915–1992). Exile, the central theme of his work, is not only an existential experience but also a geopolitical reality that determines a quest for identity and transcendence. The author analyzes how Horia transforms the experience of exile into a spiritual journey, where religion becomes an instrument of survival and inner regeneration. The aim of the research is to highlight the ways in which faith and religious symbolism shape Vintilă Horia’s worldview and his literary characters. The study is based on textual analysis of the writer’s main novels, including God Was Born in Exile, The Journey to San Marcos, A Woman for the Apocalypse, The Keys of Twilight, and The Impossibles. The methods used combine thematic and symbolic analysis with a comparative literary perspective, placing Horia within the broader framework of European exile literature. The findings reveal three major dimensions of religiosity in Horia’s work: pilgrimage, as a metaphor for spiritual and identity-seeking journeys; religion as escape, serving as a mode of salvation in the face of historical time; and finally, spiritual love, embodied in the female figure assimilated to the homeland. Through these motifs, the writer builds a universe in which salvation, faith, and memory become means of resistance against loss and alienation. In conclusion, Georgeta Orian demonstrates that, for Vintilă Horia, religion transcends the dogmatic sphere: it constitutes a vital principle of self-recreation and cultural continuity in exile.